The Impact of Milk and Its Components on Epigenetic Programming of Immune Function in Early Life and Beyond: Implications for Allergy and Asthma - Esch, Betty C. A. M. van; Porbahaie, Mojtaba; Abbring, Suzanne; Garssen, Johan; Potaczek, Daniel P.; Savelkoul, Huub F. J.; Neerven, R. J. Joost van (Frontiers in Immunology, 2020)
Specific and adequate nutrition during pregnancy and early life is considered as an important factor to redirect the increase in non-communicable diseases (NCD) such as obesity, type 2 diabetes, cardiovascular disease, cancers, and chronic allergic diseases. Epidemiologic and experimental studies have shown that nutrition is important in all stages of life but especially in early life like prenatal and the first years of life. During the last decade there is a growing interest in the potential role of epigenetic mechanisms in the increasing health problems of NCD. Epigenetics involves several mechanism including DNA methylation, histone modifications, and microRNAs which can modify the expression of genes. In the current review we focus on environmental factors which contribute to epigenetic mechanisms underlying persistent programming of immune functions, especially maternal nutrition, milk and its components.